2017
DOI: 10.1080/14786419.2017.1378214
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial and antioxidant potential of fractions and isolated compounds from Nectandra cuspidata

Abstract: The effects on the viability of promastigote and amastigote forms of Leishmania (Leishmania) amazonensis and citotoxicity in J774.A1 macrophages of ethanolic extract, fractions and isolated compounds that were obtained from the leaves of Nectandra cuspidata were determined. The total phenolics content (TP) and antioxidant activity were assessed using different assays. The ethyl acetate fraction (EAF) had the best antiproliferative activity (amastigote IC: 4.42 ± 0.60 μg/mL, promastigote IC: 33.33 ± 0.78) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Other authors report the antioxidant potential for species of the genus. Ferreira et al (2018) found high activity for Nectandra cuspidata leaves with a IC50 of 6.54 ± 0.10 µg.mL -1 . In studies on Nectandra grandiflora, Silva et al (2018) observed inhibition of about 80% of the DPPH • radical.…”
Section: Resultsmentioning
confidence: 92%
“…Other authors report the antioxidant potential for species of the genus. Ferreira et al (2018) found high activity for Nectandra cuspidata leaves with a IC50 of 6.54 ± 0.10 µg.mL -1 . In studies on Nectandra grandiflora, Silva et al (2018) observed inhibition of about 80% of the DPPH • radical.…”
Section: Resultsmentioning
confidence: 92%
“…amazonum [ 41 ], N . cissiflora [ 42 ], vitexin, isovitexin, and epicatechin in Nectandra cuspidata [ 43 ] and quercetin-3- O -rhamnoside in Nectandra grandiflora [ 44 ]. Thus, the other compounds of the Nectandra genus identified herein (peak 1, 3, 4, 5, 6, 7, 9, 10, 11, 13, 14, 15, 16, 18, 21, 22 and 23 ) are described for the first time, demonstrating the capacity of N .…”
Section: Resultsmentioning
confidence: 99%
“…Although not effective in Leishmania parasites, the NMR spectra of J. gossypifolia extracts were analyzed suggesting the occurrence of flavonoids. Recently, the leishmanicidal activity of the flavonoids isovitexin and vitexin was analyzed against promastigote and amastigote forms of L. (L.) donovani and L. (L.) amazonensis , being more effective against the visceral than the cutaneous counterpart [54, 55]. Furthermore, orientin-containing fraction from Cecropia pachystachya altered L. (L.) amazonensis viability by interfering in the mitochondrial-kinetoplast complex and inhibiting parasite arginase enzyme [56].…”
Section: Discussionmentioning
confidence: 99%